PENGARUH KOMUNIKASI ORGANISASI TERHADAP EFEKTIVITAS KERJA APARAT DI KANTOR KELURAHAN ARATENG KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Suraswati Suraswati; Kamaruddin Sellang; Monalisa Ibrahim (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the effect of Organizational Communication on the Work Effectiveness of Apparatus in the Arateng Village Office, Sidenreng Rappang District. The population of this study was 2,133 people and a sample of 32 people. The sampling technique used is saturated samples. This type of research is quantitative descriptive. Data collection techniques are observation, interviews, library research and questionnaires. Data analysis techniques using descriptive analysis, data quality tests (validity and reliability), classic assumption tests, linear regression and hypothesis testing.The results showed that organizational communication 62.68% influential categories include wise and politeness 61.8%, feedback acceptance 63%, information sharing 60%, giving information assignments 66.8%. reduce task uncertainty 61.8%. work effectiveness 61.4% influential categories include the quantity of work 61.8%, work quality 62.4%, time utilization 60.%. The factors that influence organizational communication 58.26% are quite influential include horizontal communication 62.4%, diagonal communication 56.2%, vertical communication 56.2%. This shows the effect of Organizational Communication on the Effectiveness of Workers in the Arateng Village Office Sidenreng Rappang District is 61% of the 100% expected results, which is classified in the category of